2011
DOI: 10.1159/000329295
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acid Inhibition on Esophageal Mucosal Injury Induced by Low-Dose Aspirin

Abstract: Background and Aim: Aspirin enjoys widespread use as an antithrombotic drug, but such ubiquity also increases the risk of gastrointestinal mucosal injury. Recent studies have shown that aspirin can also induce esophageal mucosal injury. We resolved to determine the intragastric pH value necessary to prevent aspirin-induced esophageal mucosal injury. Methods: 15 healthyJapanese volunteers were dosed for 7 days in a four-way random crossover trial with 100 mg entero-coated type aspirin only once daily, 100 mg as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…LDA causes not only gastric mucosal injury, but also esophageal and small bowel mucosal injury [3,7]. In our study, esophageal and gastric mucosal lesions were observed in 52 and 93% volunteers, respectively, on LDA treatment for 7 days [4,5,6,7], suggesting that LDA may be a risk factor for esophageal mucosal injury.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…LDA causes not only gastric mucosal injury, but also esophageal and small bowel mucosal injury [3,7]. In our study, esophageal and gastric mucosal lesions were observed in 52 and 93% volunteers, respectively, on LDA treatment for 7 days [4,5,6,7], suggesting that LDA may be a risk factor for esophageal mucosal injury.…”
Section: Introductionmentioning
confidence: 54%
“…Epidemiological studies of aspirin users to investigate relationship between the incidence of esophageal injury and LDA intake are limited in number [3,6,7,22,23,24,25,26,27,28], Lanas and Hirschowitz [22] were the first to demonstrate that 62% of GERD patients undergoing endoscopy were currently taking LDA, whereas only 26% of controls without GERD reported LDA use. Although half of the previous studies did not find a significant relationship with esophageal injury with mucosal break and LDA intake [23,24,25,26,28], there was no study which investigated risks for development of color changes without mucosal breaks at the EC junction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations